Innovative circular business model as a tool for applying rational consumption of the natural resource landscape - Gavkalova, Nataliia; Martin, John; Shmygol, Nadiia (Frontiers in Environmental Economics, 2025)
Economic growth within the traditional linear production model increases environmental pressure, depleting resources, and raising pollution levels. In contrast, the circular economy promotes closed production cycles, ensuring the repeated use of extracted resources. However, transitioning to this model requires active innovation adoption. Despite its rising popularity, circular economy concepts remain underdeveloped scientifically, lacking formulated models that comprehensively address implementation in both public and private sectors. This study aims to theoretically and practically substantiate the development of an innovative circular business model as a tool for rational natural resource consumption. Achieving this requires a multidisciplinary approach, integrating business models, technological innovations, and stakeholder collaboration. The paper formulates theoretical base for the natural resource landscape and proposes a model for implementation the circular economy in private and public sectors. The research also highlights barriers of implementation circular economy models.JEL classification: Q01, Q55, Q56